A test of market efficiency when short selling is prohibited: A case of the Dhaka Stock Exchange - Maria Sochi; Steven Mark Swidler (Journal of Risk and Financial Management, 2018)
A ban on short selling exists on several exchanges, especially in emerging markets. In most cases, short selling has always been prohibited, thus making it difficult to examine the ban's effect on price discovery. In this paper, we consider data from the Dhaka Stock Exchange (DSE) to test for a short selling ban on market efficiency. The analysis examines runs in daily stock returns and then forms a distribution of return clusters according to their duration. Using Monte Carlo simulation, we find that runs of longer duration appear more frequently in the DSE data than we would expect in efficient markets. We compare these results to stocks in the Dow Jones Industrial Average (DJIA). We find that the same runs tests accord with market efficiency for liquid and easily shorted DJIA stocks.
Keywords: 330; emerging market exchange; market efficiency; non-parametric tests of efficiency; Monte Carlo simulation